Ecotourism and community participation in the homestay programme of Sukau village: long-term or limited benefits? - Rosazman Hussin (Faculty of Arts and Social Sciences, University of Malaya, 2008)
The homestay programme first launched in 1995 in Temerloh in Pahang as part of a drive to promote ecotourism with community participation has since taken root in many other states. This study examines the impact of the homestay programme in the village of Sukau, 134 km from the city of Sandakan. The homestay programme was launched officially by the Sabah Ministry of Tourism, Culture and Environment on 9 September 2000 to promote ecotourism and to provide support for rural community development. The programme was introduced in Sukau village in the same year but the participants were only active and ready to receive visitors in 2002. The findings of the research show that a majority of the respondents agree that ecotourism development could offer the villagers economic benefits such as new job opportunities, improved family income, and to some extent an improved standard of living. The findings, however, also indicate that these economic benefits are limited because the vast majority of local people are still not involved in the programme.